Vulvar intraepithelial neoplasia associated with HPV infection: clinical, diagnostic, therapeutic and prophylactic aspects: A review - Anna N. Mheryan; Niso M. Nazarova; Vera N. Prilepskaya (IP Berlin A.V., 2023)
The analytical review presents data from the world literature, which discusses the relevance of vulvar intraepithelial neoplasia associated with human papillomavirus (uVIN). The incidence of uVIN is steadily increasing, especially in young women, and 1011.2% of cases can progress to vulvar carcinoma. More than 50% of uVIN cases are associated with anogenital diseases associated with the human papillomavirus, which determines the need for a comprehensive assessment and proper treatment of uVIN patients.